2017
DOI: 10.3892/etm.2017.5617
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin ameliorates cisplatin-induced cardiotoxicity via inhibition of ROS-mediated apoptosis

Abstract: Oxidative stress and apoptosis serve an essential role in cisplatin-induced cardiotoxicity, which limits its clinical use, and increases the risk of cardiovascular disease. As a natural drug, the antioxidant and antitumor effects of cyanidin have been recognized, but its protective effect on cisplatin-induced cardiomyocyte cytotoxicity remains unclear. H9c2 cells were treated with cisplatin (1–40 µM) in the presence or absence of cyanidin (40–80 µM), subsequently; oxidative stress, apoptosis and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
(31 reference statements)
3
29
0
Order By: Relevance
“…Evidence has shown that cisplatin chemotherapy can lead to cardiotoxicity (8,26). This is in agreement with the present study where cisplatin significantly inhibited cell viability and induced apoptosis of rat cardiomyocytes.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Evidence has shown that cisplatin chemotherapy can lead to cardiotoxicity (8,26). This is in agreement with the present study where cisplatin significantly inhibited cell viability and induced apoptosis of rat cardiomyocytes.…”
Section: Discussionsupporting
confidence: 94%
“…Cardiomyocytes are mitochondria-rich cells. Cardiac mitochondrial dysfunction often occurs upon ROS accumulation and overproduction caused by cisplatin, which results in disruption of mitochondrial membrane potential and release of pro-apoptotic factor (8). In the present study, loss of ΔΨm and release of cyto-c into cytosol were observed in rat cardiomyocytes treated with cisplatin.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Excessive ROS accumulation would damage cellular macromolecules such as proteins through activation of a series of signaling cascades, including mitochondrial, apoptotic and PI3K/Akt pathways [27]. When cisplatin accumulates in the mitochondrial matrix, it causes a large amount of ROS production and mitochondrial dysfunction, leading to increased mitochondrial permeability, pro-apoptotic factor release and initiate apoptosis [29]. The Bcl-2 family of proteins has a crucial role in the apoptotic mechanism of mitochondrial pathway [30], which includes pro-apoptotic protein Bax and antiapoptotic protein Bcl-2 [31].…”
Section: Discussionmentioning
confidence: 99%